Flexible insurance scheme for horticultural farmers adopted by the Government of Uruguay and still ongoing after 6 years, covering most of the country’s horticultural regions (total 1,500 hectares) - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Over the 2013-16 period, IFPRI researchers designed and piloted a flexible insurance scheme covering horticultural farmers against excess rainfall around the time of harvest, in partnership with Uruguay’s Ministry of Livestock, Agriculture, and Fisheries and a public insurance company. The government adopted the insurance scheme, with all the features recommended by the pilot’s findings, and has successfully sold it to farmers over the past six years.